STEREOTACTIC INSTRUMENT IN CT GUIDED BIOPSY - RUAMTHANTONG, Anuchit; THATRINARANONTASIN, Thiti; PRABHASAVAT, Krisdee; JITBANCHUEN, Suwana; CHARNCHAOWANICK, Panida; KARUWANARINT, Supawadee; WISESTSANG, Venus (The ASEAN Journal of Radiology, 2023)
We have designed a basic and simple instument for CT-guided biopsy, attached to the CT-table. The instrument is easy to be used and can be learned how to use in a short time. We use this instrument for CT-guided biopsy in 6 cases with good accuracy of 100 % and no major complications We believe that the procedures with this instrument when used as an aid to the CT-biopsy would improve the safety, accuracy and the value of percutaneous biopsy in the radiology department.